Myeloid dendritic cells and periodontal disease association: integrated study of single-cell sequencing and Mendelian randomization analysis - Shi, ChengJi; Ou, XinYi; Lei, XiaoXu; Huang, LiJuan; Xu, ShuHao; Li, Wei; Zhao, Xi (Frontiers in Immunology, 2025)
BackgroundPeriodontal disease is a widespread inflammatory condition that compromises the supporting structures of the teeth, potentially resulting in tooth loss if left untreated. Despite advancements in therapeutic interventions and an enhanced understanding of its pathophysiology, emerging techniques such as single-cell RNA sequencing (scRNA-seq) and Mendelian randomization (MR) present new opportunities for precision medicine in the management of periodontal disease.MethodsData derived from the GSE152042 dataset underwent rigorous quality control, normalization, and dimensionality reduction using Seurat and the MonacoImmuneData framework. Marker genes were identified to delineate subgroups for subsequent analysis utilizing CellChat and ClusterProfilerR. MR analysis of the expression quantitative trait loci (eQTLs) for these genes was conducted to determine causal relationships with periodontal disease, leveraging data from the IEU Open GWAS project.ResultsSingle-cell analysis revealed distinct immune cell subtypes and indicated an increased presence of myeloid dendritic cells (mDCs) in patients with periodontal disease. MR analysis identified twenty-six significant genes, with LIMA1 (LIM domain and actin-binding 1) demonstrating a robust causal association with the progression of periodontal disease. Gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses highlighted crucial pathways involved in periodontal inflammation and tissue destruction. Visualization at the single-cell level elucidated the role of LIMA1 in disease progression, alongside differences in cell communication dynamics between LIMA1-positive and -negative populations.ConclusionThis study underscores the utility of scRNA-seq and MR in elucidating essential factors in the pathogenesis of periodontal disease, thereby reinforcing the necessity for targeted therapeutic strategies. The identification of LIMA1 as a pivotal gene in periodontal disease progression opens new avenues for precision medicine approaches, potentially enhancing treatment efficacy and patient outcomes in periodontal management.